2007
DOI: 10.1097/opx.0b013e3180dc99a8
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measurements of Lower-Level Visual Stress

Abstract: The results suggest that the squint-beneficial conditions are operated by a local mechanism involving contraction of the orbicularis and increase in reflex blinking, whereas those that do not benefit from squint do not engage the orbicularis and decrease blink, possibly through central inhibition of spontaneous blinking. The EMG response is a sensitive objective measure for the squint-beneficial conditions. However, for the non-squint-beneficial conditions, blink rate may be a more sensitive objective measure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 22 publications
4
15
1
Order By: Relevance
“…Other studies have extended over one to two hours and averaged values may have been derived from dividing a recording period into shorter intervals of one to five minutes, for example. Some studies provide details of the methods clearly indicating that the subjects were seated, while being evaluated in an experimental room or chamber, while others have asked subjects to be seated while supporting their head on some type of chin rest during recording . In line with previous studies, the group 1 subjects were seated in a high‐back comfortable chair to hopefully minimise head movement as they were being assessed and asked to direct their gaze toward a high contrast target on the white (wall) board in front of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have extended over one to two hours and averaged values may have been derived from dividing a recording period into shorter intervals of one to five minutes, for example. Some studies provide details of the methods clearly indicating that the subjects were seated, while being evaluated in an experimental room or chamber, while others have asked subjects to be seated while supporting their head on some type of chin rest during recording . In line with previous studies, the group 1 subjects were seated in a high‐back comfortable chair to hopefully minimise head movement as they were being assessed and asked to direct their gaze toward a high contrast target on the white (wall) board in front of them.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a three minute ‘adaptation’ period or perhaps even a five minute ‘accommodation’ period, followed by just two minutes for calculation of blink rates. Similarly, the SBR could progressively increase (or decrease) from initial values especially under extended periods of observation and with subjects required to undertake prescriptive visual tasks or are being exposed to visual glare …”
mentioning
confidence: 99%
“…Wetting agents are often added to help retain lens moisture and alleviate symptoms of dry eye 16,17 . Previous studies have shown that different LCSs afford different ‘wettability,’ a term referring to the ability to help retain moisture to the surface of contact lenses, often by mitigating their hydrophobic tendency 18 . Differences in ‘wettability’ of LCSs could play a significant role in determining the frequency of eye blinks and ocular discomfort, especially for performing visually demanding tasks on a computer screen.…”
Section: Introductionmentioning
confidence: 99%
“…As visual fatigue is defined as a decrease in performance of the human vision system produced by a physiological change, it may be desirable to use EMG to detect muscle activities around the eyes and find a relationship with visual fatigue/discomfort. Nahar et al [59] studied the EMG response of the orbicularis oculi muscle to "low-level visual stress" conditions, where "low level" means the work conditions in which muscles are activated at a level that can be maintained for a long period of time. The results showed that for conditions in which visual fatigue may stem from eyelid squinting (e.g., refractive error, glare), the power of the EMG response increased with the degree of eyestrain.…”
Section: Electromyographymentioning
confidence: 99%